Emotional Design applied in the analysis of patient experience in oncology services. Case study - Sañudo, Yeray; Aguado-González, Laura; Sierra-Pérez, Jorge (Jornada de Jóvenes Investigadores del I3A, 2025)
Oncology services are complex and emotionally demanding for patients. Understanding the patient experience is key to improving the process. This study proposes a new methodology for measuring emotional reactions from an Emotional and Service Design perspective.